Albuquerque and the City manager plan 1917 - 1948 (Albuquerque, New Mexico Division of research Department of Government UNM, 1951)
This study of city government adds significantly to the critical analyses of institutions in operation, Moreover, in describing the Albuquerque manager system.
Information book on Albuquerque and the City Managers Plans from 1917 - 1948.
Master list item # 5
File location is in the New Mexico Cities and Towns
Keywords: Albuquerque, New Mexico; The commission manager plan; Albuquerque's city government under the commission manager plan; Benchmarks and new sirections; An evaluation of the manager plan in Albuquerque; Chart and table organization chart, City of Albuquerque; Terms of city commisioners and city managers 1917 - 1948